Analysis Of Corporate Income Tax Calculation and Reporting On Companies Drinking Water Area (PDAM) Parepare City - Sariana Damis; Hernianti Harun; Nurwani M; Fatimah Fatimah; Fitri Ani (Universitas Muhammadiyah Makassar, 2024)
Corporate income tax is a tax imposed on income from the operational activities of PDAM Parepare City where the income in question is any additional economic ability received or obtained by PDAM Parepare City. Data collection techniques are carried out by means of observation, interviews and documentation. The data analysis technique uses interpretive qualitative methods. This method is an attempt to find an explanation of social or cultural events based on the perspective and experience of the person being researched. The results of the study show that the method of calculating Taxable Income carried out by PDAM is in accordance with the applicable tax law regulations. Over the past three years, the development of corporate income tax at PDAM Parepare City in 2018-2020 has fluctuated, where in 2019 there was a decrease in the tax burden and in 2020 there was an increase in the corporate income tax burden.